Information mediation in the organizational context: the role of communication and information technologies - Moraes, Silvana De Souza; Martins Damian, Ieda Pelogia [UNESP] (Univ Fundacao Mineira Educacao & Cultura-fumec, 2020)
This study aims to present a literature review on the subject of information mediation, especially in the organizational context influenced by information and communication technologists (ICT). The concepts of the mentioned themes were revised and the results show that a new scenario is presented in the mediation of information with the help of ICTs and a new post-custodial paradigm of information demands from organizations new forms of information production, dissemination, mediation and use., making efforts for collaboration among information users.
Keywords: Mediation; Information; Information Technology; Comunication